Isothermal Microcalorimetry of Tumor Cells: Enhanced Thermogenesis by Metastatic Cells - Lemos, Douglas; Oliveira, Thaís; Martins, Larissa; de Azevedo, Vitória Ramos; Rodrigues, Mariana Figueiredo; Ketzer, Luisa Andrea; Rumjanek, Franklin David (Frontiers in Oncology, 2019)
Tumor cells exhibit rewired metabolism. We carried out comparative analyses attempting to investigate whether metabolic reprograming could be measured by isothermal microcalorimetry. Intact metastatic cell lines of tongue cell carcinoma, human and murine melanoma, lung, and breast tumors consistently released more heat than non-metastatic cells or cells displaying lower metastatic potential. In tongue squamous carcinoma cells mitochondrial enriched extract reproduced the heat release pattern of intact cells. Cytochalasin D, an actin filament inhibitor, and suppression of metastasis marker Melanoma associated gene 10 (MAGEA10) decreased heat release. Uncoupling protein 2 was highly expressed in metastatic cells, but not in non-metastatic cells. Carnitine palmitoyl transferase-1 inhibitor, Etomoxir strongly inhibited heat release by metastatic cells, thus linking lipid metabolism to thermogenesis. We propose that heat release may be a quantifiable trait of the metastatic process.